Perbedaan Locus Of Control Ditinjau dari Etnis - Eko Sujadi; Leni Setioningsih (Jurnal Bimbingan dan Konseling Terapan, 2018)
In behaving towards what happens in him, man will be oriented in two directions, there are individuals who believe that what happens to him is the result of his own efforts, on the contrary there are individuals who believe that the events that occur are influences from outside the self. This belief is called the locus of control. Each individual has a difference in the locus of control. This difference is influenced by several factors, one of which is ethnicity. This study aims to describe the locus of control of individuals belonging to the ethnic Kerinci, Java and Minang, and reveal differences in the locus of control of the three ethnic groups. This research uses quantitative approach with descriptive and comparative method. The sampling technique used is simple random side with total number 230 students. The instrument used is Internal Rotters inventory -External Locus of Control (I-E Scale). Data were analyzed by using descriptive statistics and one way anova. The findings of this study include: 1) locus of control of ethnic Javanese students tend to external, while ethnic Kerinci and Minang reside in internal. However, the third locus of control score is not far behind the median locus of control; and 2) there are differences in locus of control of students who have ethnic Kerinci, Java and Minang. The researcher suggested to the Counselor Teacher / Counselor to always pay attention deeply and sensitively to the condition of the foster students, including the locus of control aspect. These efforts can be made by applying several counseling services with certain approaches that are theoretically proven effective in forming an internal locus of control. Parents should also provide understanding to the children about all the events that happen to him and how to react. Subsequently to other researchers, the results of this research need to be addressed and followed up by adding samples and considering some other characteristics, such as gender, age, social demography, economic and family status, religion, and others.